Environmental Factors, Gross Regional Domestic Product, and Underemployment in Indonesia - Nugraha Pratama; Ahmad Syaifullah (Ecoplan, 2026)
This study examines the relationship between forest fires, environmental quality, and regional economic performance on the underemployment rate in Indonesia, highlighting a limitation in the existing literature that tends to assume a direct relationship between environmental factors and labor market outcomes. In the context of developing economies characterized by a dominant informal sector, this study argues that environmental impacts on the labor market are not direct, but rather operate through adjustment mechanisms such as productivity changes and working hours. Using panel data covering 30 provinces over the period 2015–2024 and employing a Fixed Effects Model (FEM), the results show that environmental and economic variables jointly influence underemployment; however, only GRDP has a statistically significant and negative partial effect. Meanwhile, forest fire and environmental quality variables are not statistically significant. The negative coefficient of forest fires suggests the presence of labor market adjustment mechanisms or reflects underlying land-based economic activities that do not fully capture the direct environmental impact. The main contribution of this study lies in demonstrating that the underemployment indicator has limitations in capturing environmental impacts that are indirect, lagged, and spatially uneven. Therefore, this study offers a reinterpretation of the relationship between environmental factors and the labor market, where economic factors play a dominant role in the short run, while environmental factors operate through structural channels over the long term.